(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study analyzes the conceptual meaning of the verse "ihdinashiroothol mustaqim" (QS. Al-Fatihah: 6) in Tafsir Faid ar-Rahman by Kyai Sholeh Darat, this interpretation uses the concept of tahlili (analytic) to examine the interpretation of zahir (general) and batin (isyari) intended for the Javanese lay public. With the research question of how the conceptualization of "Shirathal Mustaqim" and the classification of guidance in this interpretation. This article uses a descriptive-analytical method based on literature review (library research), summarizing biographical data and critical analysis of the interpretation works. The main findings show that in zahir, "Shirathal Mustaqim" is interpreted as the path of the Prophets which requires total obedience, and is divided into the path to Heaven (for "Ashab al-Yamin") and the path to Allah (for "As-Sābiqūn al-Muqarrabūn"). Spiritually (inner), Kyai Sholeh Darat classifies guidance into three levels: “Hidayah al-’Ām”, “Hidayah al-Khāsh”, and “Hidayah al-Akhash” (the essence), where the true path (al-Shirath al-Haqiqi) from servants to God is described as difficult and blocked by Satan, while the path from God to servants is described as easy, safe, and with the Prophets and righteous.